Keterkaitan Status Hukum Amal Saleh dan Surga dalam Perspektif Al-Qur’an - Madany, A. Malik (UIN Sunan Kalijaga, 2014)
The stipulation to go to heaven is belief (faith). The perfect belief will motivate the believers to do the goodness. Nevertheless, the goodness is not enough, it takes gift and blessing of Allah to perfectly and well concreate it. Such belief is very needed by human being so that they can avoid arrogance and excessive self confident of their charity. However, human being cannot get achievement in their life except by Allah guidance.